216 : (16 - х) = 18 5у + 3(7у + 18) = 106
16 - х = 216 : 18 5у + 21у + 54 = 106
16 - х = 12 26у = 106 - 54
х = 16 - 12 26у = 52
х = 4 у = 52 : 26
у = 2
8х + 4(13х + 32) = 308 5(11х - 31) - 9х = 121
8х + 52х + 128 = 308 55х - 155 - 9х = 121
60х = 308 - 128 46х = 121 + 155
60х = 180 46х = 276
х = 180 : 60 х = 276 : 46
х = 3 х = 6
(5 – 3b) + (3b – 11)=5-3b+3b-11=-6
5b – (6b + a) – (a – 6b)=5b-6b-a-a+6b=5b-2a
2(y – 1) – 2y + 12=2y-2-2y+12=10
16 + 3(2 – 3y) + 8y=16+6-9y+8y=22-y
3 – 17a – 11(2a – 3)=3-17a-22a+33=36- 39a
(2a – 7y) – (5a – 7y)=2a-7y-5a+7y=-3a
14b – (15b + y) – (y + 10b)=14b-15b-y-y-10b=-11b-2y
7(5a + 8) – 11a=35a+56-11a=24a+56
9x + 3(15 – 8x)=9x+45-24x=45- 15x